Clinical or Imaging Diagnosis of the Current Medical Practice for Superior Vena Cava Syndrome? - Liliana Dragomir; Virginia Marina; Mihaela Anghele; Aurelian-Dumitrache Anghele (Diagnostics, 2021)
Most cases of superior vena cava syndrome are easily diagnosed bya clinical examination alone, but several diagnostic tests and procedures can be helpful. When a patient presentswith a suspected diagnosis of superior vena cava syndrome, the first step is to obtain an imaging study that confirms the diagnosis and aids treatment decisions. Magnetic resonance imaging, contrast-enhanced CT scanning, radionuclide flow studies and traditional venography are all appropriate techniques. Still, the CT scan is the most readily available technology in most centers. The CT scan and magnetic resonance imaging also provide information on possible etiologies and can therefore direct the approach towards a tissue diagnosis.